Earth and Planetary Surface Processes Perspectives on Integrated, Coordinated, Open, Networked (ICON) Science. Issue 8 (15th August 2022) - Burberry, C. M.; Flatley, A.; Gray, A.; Guilinger, J.; Hamshaw, S.; Hill, K.; Mu, Y.; Rowland, J. C.
Abstract: This article provides a commentary about the state of integrated, coordinated, open, and networked (ICON) principles in Earth and Planetary Surface Processes and discussion on the opportunities and challenges of adopting them. This commentary focuses on the challenges with current inclusive, equitable, and accessible science and highlights how research undertaken in the earth and planetary surface processes community currently benefit from and would be able to grow as a discipline with more directed implementation of ICON principles. Key Points: The study of Earth and planetary surface processes would benefit from the further advancement and application of Integrated, Coordinated, Open, Networked (ICON) and justice, equity, diversity, and inclusion principles An important aspect of ICON is that science effectively serves both the scientific communities and broader society This commentary highlights current and future application of ICON principles within the Earth and planetary surface processes community